Մանիպուլյացիոն կառավարման ազդեցությունը հասարակական կարծիքի վրա - Քալանթարյան, Էդգար (YSU Journal of International Affairs, 2018)
The regulation and integration of modern society are the most important among the functions of political power. Their implementation depends on the regular and successful influence of political structures on the mass consciousness and psychology having a purpose to legitimate all decisions in the public sector. Thus, constantly growing pressure on mass consciousness and public opinion accompanied by psychological and ideological influence. According to research, today there are plenty of ways or "soft measures" to influence the wide groups of public and these are usually latent. This phenomenon is manipulation. Manipulation has many ways of influencing the public opinion and their use implies considerable success for those who apply to them. Consequently, it transforms into a socio-political reality making an influence on all areas of social activities.
Keywords: social opinion, manipulative governance, political community, society, political myths, the manipulation of human consciousness, public self-consciousness, political manipulation